Camouflaged Indicators of Earnings Management. Issue 2 (14th March 2020) - Kama, Itay; Melumad, Nahum
Abstract: We argue that, in response to increased scrutiny and greater attention to accruals versus sales, firms become more likely to engage in accrual conversion (AC) cash management aimed at aligning cash and accruals with earnings and sales (e.g. by factoring of receivables). In doing so, they reduce the statistical power of standard indicators of accrual-based earnings management – in effect, camouflaging their earnings management activity. This proposition is of interest because many influential papers on earnings management have utilized accrual-based indicators to reach their conclusions. Our results indicate that firms indeed became more likely to engage in AC cash management after the passage of the Sarbanes-Oxley Act (SOX), and that this tendency was particularly pronounced among firms with strong incentives (or enhanced ability) to perform and hide earnings management. In particular, our findings suggest that the post-SOX decrease in standard measurements of accrual-based earnings management, identified in prior research, is partially attributable to firms' increased engagement in AC cash management activity.